The Strategic Implication of Artificial Intelligence on Freelancing in Bangladesh: A Literature Review (IUBAT Review, 2024)
This study critically analyzes the strategic impact of Artificial Intelligence on freelancing in Bangladesh. Using a systematic literature review, data was gathered from scientific articles available on platforms such as Google Scholar, SSRN, Wiley database, as well as reports from PricewaterhouseCoopers International Limited (PwC). The findings highlight strategic implications using a Strengths, Weaknesses, Opportunities, and Threats (SWOT) framework. AI presents a potential threat to freelancers, as some job roles can now be replaced by AI technology. The authors also highlight that the current lack of AI-related skills is a weakness but could also be seen as an opportunity for upskilling. This underscores the importance of enhancing skills to manage and optimize AI systems effectively. Additionally, AI has created opportunities in expanding AI-related job sectors in Bangladesh, supported by global AI trends, increasing government recognition of freelancing, new job creation, and improved productivity. Among these factors, AI acceptance, government recognition, and productivity enhancements can be considered strengths. The practical implications suggest that freelancers and policymakers alike can leverage these strategic insights to enhance the Bangladeshi freelancing sector. This study's further emphasize potentials for AI skills development, aiding the growth of freelancing careers. While existing studies tend to focus on AI's benefits and risks, few explore the strategic implications within the Bangladeshi freelancing context. Academics, policymakers, freelancers, and other stakeholders invested in advancing digital Bangladesh should engage in further research on developmental pathways for upskilling and supporting freelancing as a robust sector.IUBAT Review—A Multidisciplinary Academic Journal, 7(2): 100-113